Keep an Eye Out for Myasthenia Gravis Patients with an Eye Out - Leis, A. Arturo; Moore, Alan R. (Frontiers in Neurology, 2014)
Eye trauma and blindness are common in the United States, with an incidence of over 2 million cases per year and 25 million blind adults, respectively. However, literature is surprisingly scarce on the potential confounding effect of eye trauma or blindness on the diagnosis of myasthenia gravis (MG), an autoimmune neuromuscular disease in which fluctuating ocular symptoms are the most distinguishing feature. We present the case of a 75 year-old man with eye enucleation referred for electrodiagnostic evaluation of the right upper limb after an accidental fall. Neurological examination showed proximal muscle weakness, but MG was not initially considered because the patient lacked the classic ocular symptoms of MG. The delay in diagnosis resulted in worsening of systemic MG symptoms, although in other patients it may have precipitated MG crisis or possibly death. Greater awareness that eye trauma or blindness can prevent expression of ocular symptoms in neuromuscular disorders is needed to avoid morbidity associated with an erroneous or delayed diagnosis.